Smart working after the pandemic - Iacci, Paolo (Community Notebook. People, Education and Welfare in the Society 5.0, 2021)
To withstand the impact of the pandemic, companies implemented new organisational forms in record time, among which remote working and e-commerce stand out. Especially remote working, hastily renamed smart working or agile working, has found an extension hardly imaginable before the pandemic. In fact, people, in most cases using their own personal equipment, have tried to do the same things from home that they used to do in the office.